2015
DOI: 10.3923/ajft.2015.118.126
|View full text |Cite
|
Sign up to set email alerts
|

Utilization of High Quality Extracted Olive Oil in Manufacture of Modified Butter Blends

Abstract: Olive oil (Olea europaea L.) which extracted by pressure system from Koroneiki olive fruit variety by using 2% NaCl during malaxation step was used in manufacture of modified butter blends. Different ratios (5, 10, 15 and 20% w/w) olive oil/butter oil were applied to serve 4 treatments (A, B, C and D). The resultant modified butter blends were stored at 5±1°C for 6 weeks and assayed for organoleptic, physical and chemical properties. Obtained results showed that Free Fatty Acids (FFA) contents were increased b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
3
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 14 publications
2
3
0
Order By: Relevance
“…The SFAS were decreased in all samples. These results correspond with Hassan et al (2015) who reported that increasing the level of Palme oil in butter oil, the SFA decreased while oleic and linoleic acid were increased. (Manuela et al 2011) recommend reducing SFA with replacing USFA in the diet.…”
Section: Fatty Acids Of Table Margarine ( Tm)supporting
confidence: 91%
See 2 more Smart Citations
“…The SFAS were decreased in all samples. These results correspond with Hassan et al (2015) who reported that increasing the level of Palme oil in butter oil, the SFA decreased while oleic and linoleic acid were increased. (Manuela et al 2011) recommend reducing SFA with replacing USFA in the diet.…”
Section: Fatty Acids Of Table Margarine ( Tm)supporting
confidence: 91%
“…In all sample PV gradually significant increased along storage period to reach between 1.25 to 2.13 meq O2/Kg at the end of cold storage. This finding confirmed with ( Hashempour-Baltork et al 2017 andHassan et al 2015 Firmness and stickiness of TM.…”
Section: Peroxide Value (Meq O2/kg Oil)supporting
confidence: 80%
See 1 more Smart Citation
“…Cultures were propagated in sterile skim milk at 37°C. Olive oil was extracted by pressure system from Koroneiki olive fruit variety by using 2% NaCl during malaxation step as mentioned by Hassan et al (2015). Its properties were as follow in Table 1.…”
Section: Methodsmentioning
confidence: 99%
“…Dairy Sci., 10 (6): 288-296, 2015 several antioxidants (Ocakoglu et al, 2009). Several methods have been proposed improving oil extraction procedures including enzymatic pretreatment De Faveri et al, 2008), sodium chloride (Cruz et al, 2007;Hassan et al, 2015) and calcium carbonate (Moya et al, 2010). However, limited studies have been carried out on the utilization of olive oil in dairy products.…”
Section: Introductionmentioning
confidence: 99%